Analyzing Production Cost of Chicken and Eggs in Sri Lanka: A Rapid Assessment 2023 - Fernando, S.P.; Wijesinghe, I.P.P.M.; Ruhunuge, I.J.A.; Hitihamu, S.; Samantha, N.P.G. (Department of Economics, University of Colombo, Sri Lanka., 2024)
Recent increase in chicken meat and egg prices in Sri Lanka has been attributed to several factors. One significant issue was insufficient local production of maize, which was the main ingredient in poultry feed, resulting in a steady increase in feed prices. Additionally, the tax imposed on commercial poultry feed and feed ingredients, shortage of day-old chicks (DOCs), and improperly maintained parental stock contributed to the recent increase in chicken meat and egg prices in Sri Lanka. Hence the objectives of the study are to determine the production costs of one kilogram of chicken meat and table eggs for small-scale, medium-scale, and large- scale producers. The sample was selected using a multi-stage random sampling technique. Data was collected from September to October 2023. Eighty farms were visited including 47 chicken meat producers and 33 egg producers. The cost of production and feed cost of eggs and meat at large-scale, medium-scale, and small- scale producers were calculated separately. The total cost of production of one kilogram of chicken meat with skin was 863.69 LKR/kg for small-scale farmers and 731.99 LKR/kg for large-scale farmers whereas the cost for one kilogram without skin was 912.59 LKR/kg for small-scale farmers and 773.14 LKR/kg for large-scale farmers. The total cost of production of one egg was 34.82 LKR for large-scale and 43.81 LKR for small-scale producers.
Keywords: Cost of Production; Chicken Meat; Eggs; Large-Scale; Small-Scale